Galaxy collisions forging new worlds from cosmic crashes - Struck, Curtis (New York Springer, 2010)
Galaxy collisions are the key process in building galaxies, triggering the formation of stars and the build-up of heavy elements that allow the formation of planets and solar systems. This book presents the revolutionary research advances achieved in the last decade and lucidly explains the underlying dynamical processes. Galaxy Collisions takes a comprehensive trip through the visually spectacular world of galaxy collisions investigates the interactions of stars, gas clouds, and dark matter in galaxy collisions uses analogies and metaphors to help comprehend the bizarre world of galaxies presents recent research results to enhance the understanding of galaxy formation and evolution includes discoveries of minor collisions within our own group of galaxies shows how a galaxy collision might affect a solar system, or a planet like ours.
Preface -- Acknowledgments -- List of Illustrations -- Chapter1: Exploring the world of galaxies -- Chapter 2: Head-on collisions and rings of fire -- Chapter 3: Swinging on by: the tidal twists -- Chapter 4: Major mergers and their colossal consequences -- Chapter 5: What happens to the little guy: minor mergers -- Chapter 6: The secret of fire: triggered star formation -- Chapter 7: Not always in a galaxy far, far away -- Chapter 8: A wider view -- Chapter 9: Epilogue: the galacto-biology of collisions -- Glossary -- Resources -- Index.
Electronic reproduction.
Keywords: Galaxies; Collisions (Astrophysics).; Electronic books